2020
DOI: 10.1155/2020/9842768
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Rapid On‐Site Evaluation for CT‐Guided Percutaneous Fine Needle Aspiration in the Diagnosis of Pulmonary Occupying Lesions

Abstract: Objective. Rapid on-site evaluation (ROSE) is an effective and efficient auxiliary examination, but its value for CT-guided percutaneous fine-needle aspiration (FNA) in the diagnosis of pulmonary occupying lesions is unclear. This study is aimed at evaluating the clinical utility of ROSE for CT-guided percutaneous FNA. Methods. We reviewed 234 patients from September 2018 to April 2019. The result using ROSE was compared with the final pathological diagnosis of CT-guided percutaneous FNA, and we also compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
1
13
0
1
Order By: Relevance
“…We observed some complications such as 2 mild lung hemorrhages and 17 cases of mild to moderate pneumothoraxes, but the rate was lower than what was previously been reported [ 23 ]. The lower incidence was found with CT-guided percutaneous FNAB, and this result agrees with the reports in human medicine [ 19 , 20 ]. Nevertheless, no complications required further therapeutic intervention.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We observed some complications such as 2 mild lung hemorrhages and 17 cases of mild to moderate pneumothoraxes, but the rate was lower than what was previously been reported [ 23 ]. The lower incidence was found with CT-guided percutaneous FNAB, and this result agrees with the reports in human medicine [ 19 , 20 ]. Nevertheless, no complications required further therapeutic intervention.…”
Section: Discussionsupporting
confidence: 90%
“…In human medicine, the diagnostic accuracy of the core biopsy under CT guidance is reported between 88% [ 16 ] and 95% [ 13 ], with similar results for FNAB, 85% [ 15 ]. In the literature, it has been reported that carcinomas and round cell tumors exfoliate much better than sarcomas [ 1 ], and, since most of the malignancies reported in the lung are carcinomas [ 20 ] and in the mediastinum are lymphomas or thymomas [ 28 , 29 , 30 , 31 ], this may explain why there is quite a high accuracy with CT-guided FNAB in our study. Indeed, 29 cases were epithelial neoplasms, 28 from lungs and 1 from thymus.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…1 ROSE is recommended in the sampling process to improve diagnostic accuracy, reduce the risk of complications, and enable appropriate specimen triage. [9][10][11] With ROSE, the yield of conventional TBNA is similar to that of EBUS-TBNA and this is especially relevant in the case of sarcoidosis. 12 Even at centers where an EBUS facility is available, conventional TBNA with ROSE can provide a diagnostic yield similar to EBUS.…”
Section: Discussionmentioning
confidence: 99%